Schilderen 84. - Van den Bussche, Willy (Knokke : Cultureel Centrum Scharpoord, 1984)
Bouttens, Philippe ; Devriendt, Robert ; Gentils, Frans ; Moerman, Piet ; Sweetlove, William ; Vanderplaetsen, Wim ; Vermeersch, Rik ; Willocx, André
Schilderen 84, Cultureel Centrum Scharpoord, van 23 november tot 2 december 1984
boek